(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This is a descriptive study aimed to detect the expression of Ki67 and Her2 tumor markers in cervical tumors. Forty-five formalin fixed paraffin blocks were randomly selected from women samples previously diagnosed as cervical tumors (Thirty-five samples were malignant tumors and ten samples were benign tumors). The paraffin blocks were cut by rotary microtome and stained by immunohistochemical method for detection of Ki67 and Her2. The data obtained was analyzed using SPSS program. The malignant tumors included 29 (83%) samples were squamous cell carcinoma and remaining 6 (17%) samples were adenocarcinoma. The patient age ranged from 27 to 85 years with mean age of 57 years. From the samples 14 (31%) samples were Ki67 positive (all of them were malignant) and 31 (69%) samples were Ki67 negative (P value <0.05). The results also showed 15 (33%) samples Her2 positive (all of them were malignant) and 30 (67%) samples were Her2 negative (P value <0.05). Regarding malignant tumors 14 (40%) positive samples and 15 (43%) negative samples were squamous cell carcinoma and no positive result was found of Ki67 expression for adenocarcinoma (P value >0.05). And 10 (29%) positive samples and 19 (54%) negative samples of Her2 results were squamous cell carcinoma and 5.0 (14%) positive samples and 1 (3.0%) negative sample of Her2 results were adenocarcinoma (P value >0.05). This study concluded that the expression of Ki67 and Her2 is associated with malignant tumors of the cervix, also concluded that there was significant different between Ki67 and histopathological grade while there were no significant different between Her2 expression and the histopathological grade.